Biochip-based instruments development for space exploration: influence of the antibody immobilization process on the biochip resistance to freeze-drying, temperature shifts and cosmic radiations. Issue 2 (28th June 2016) - Coussot, G.; Moreau, T.; Faye, C.; Vigier, F.; Baqué, M.; Le Postollec, A.; Incerti, S.; Dobrijevic, M.; Vandenabeele-Trambouze, O.
Abstract: Due to the diversity of antibody (Ab)-based biochips chemistries available and the little knowledge about biochips resistance to space constraints, immobilization of Abs on the surface of the biochips dedicated to Solar System exploration is challenging. In the present paper, we have developed ten different biochip models including covalent or affinity immobilization with full-length Abs or Ab fragments. Ab immobilizations were carried out in oriented/non-oriented manner using commercial activated surfaces with N -hydroxysuccinic ester (NHS-surfaces) or homemade surfaces using three generations of dendrimers (dendrigraft of poly L-lysine (DGL) surfaces). The performances of the Ab -based surfaces were cross-compared on the following criteria: (i) analytical performances (expressed by both the surface density of immobilized Abs and the amount of antigens initially captured by the surface) and (ii) resistance of surfaces to preparation procedure (freeze-drying, storage) or spatial constraints (irradiation and temperature shifts) encountered during a space mission. The latter results have been expressed as percentage of surface binding capacity losses (or percentage of remaining active Abs). The highest amount of captured antigen was achieved with Ab surfaces having full-length Abs and DGL-surfaces that have much higher surface densities than commercial NHS-surface. After freeze-drying process, thermal shift and storage sample exposition, we found that more than 80% of surface binding sites remained active in this case. In addition, the resistance of Ab surfaces to irradiation with particles such as electron, carbon ions or protons depends not only on the chemistries (covalent/affinity linkages) and strategies (oriented/non-oriented) used to construct the biochip, but also on the type, energy and fluence of incident particles. Our results clearly indicate that full-length Ab immobilization on NHS-surfaces and DGL-surfaces should be preferred for potential use in instruments for planetary exploration.